Azimuthal separation in nearly back-to-back jet topologies in inclusive 2- and 3-jet events in pp collisions at s = 13 Te - Sirunyan, A M; Tumasyan, A; Adam, W; Ambrogi, F; Asilar, E; Bergauer, T; Brandstetter, J; Brondolin, E; Dragicevic, M; Erö, J; Del Valle, A Escalante; Flechl, M; et al. (The European physical journal. C, Particles and fields, 2019)
A measurement for inclusive 2- and 3-jet events of the azimuthal correlation between the two jets with the largest transverse momenta, Δ ϕ 12 , is presented. The measurement considers events where the two leading jets are nearly collinear ("back-to-back") in the transverse plane and is performed for several ranges of the leading jet transverse momentum. Proton-proton collision data collected with the CMS experiment at a center-of-mass energy of 13 Te and corresponding to an integrated luminosity of 35.9 fb - 1 are used. Predictions based on calculations using matrix elements at leading-order and next-to-leading-order accuracy in perturbative quantum chromodynamics supplemented with leading-log parton showers and hadronization are generally in agreement with the measurements. Discrepancies between the measurement and theoretical predictions are as large as 15%, mainly in the region 177 ∘ < Δ ϕ 12 < 180 ∘ . The 2- and 3-jet measurements are not simultaneously described by any of models.
Keywords: QCD; Jets; Physics; Azimuthal angle; CMS; MC generators